R-gene variation across Arabidopsis lyrata subspecies: effects of population structure, selection and mating system - Buckley, James (BMC Evol Biol, 2016)
BACKGROUND: Examining allelic variation of R-genes in closely related perennial species of Arabidopsis thaliana is critical to understanding how population structure and ecology interact with selection to shape the evolution of innate immunity in plants. We finely sampled natural populations of Arabidopsis lyrata from the Great Lakes region of North America (A. l. lyrata) and broadly sampled six European countries (A. l. petraea) to investigate allelic variation of two R-genes (RPM1 and WRR4) and neutral genetic markers (Restriction Associated DNA sequences and microsatellites) in relation to mating system, phylogeographic structure and subspecies divergence. RESULTS: Fine-scale sampling of populations revealed strong effects of mating system and population structure on patterns of polymorphism for both neutral loci and R-genes, with no strong evidence for selection. Broad geographic sampling revealed evidence of balancing selection maintaining polymorphism in R-genes, with elevated heterozygosity and diversity compared to neutral expectations and sharing of alleles among diverged subspecies. Codon-based tests detected both positive and purifying selection for both R-genes, as commonly found for animal immune genes. CONCLUSIONS: Our results highlight that combining fine and broad-scale sampling strategies can reveal the multiple factors influencing polymorphism and divergence at potentially adaptive genes such as R-genes. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12862-016-0665-5) contains supplementary material, which is available to authorized users.